Design and Build Microcontroller-Based Computer Numerical Control (CNC) Machine - Iqbal Rasyidin; Hamdani; pristisal (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Computer Numerical Control (CNC) machining is a system that allows automatic control of machine tools using graphically depicted commands. This study was conducted to determine and create microcontroller-based CNC machines for material processing. It is expected that the use of microcontrollers as the main control instrument will allow CNC machines to operate more flexibly and efficiently. The approach to conducting research includes conceptual planning, component selection, electronic system development, operational management, and performance evaluation. CNC machines are designed to use microcontrollers to drive stepper motors and control the motorization process using G-Code data. The findings of the study show that microcontroller-based CNC (computer numerical control) machines can produce outputs with the accuracy and pressure required for material processing applications. According to the results of the performance evaluation, the machine can operate in different time spans and customer types while providing consistent results. As a result, the use of microcontroller-based CNC machines has the potential to be an effective alternative in the development of material processing technologies with automatic controls that can be accessed and adapted for a wide range of industrial applications.